Transnationalism and Hypertension Self-Management Among Haitian Immigrants. (March 2016) - Sanon, Marie-Anne; Spigner, Clarence; McCullagh, Marjorie C.
Purpose: Transnationalism—maintenance of transborder activities—has important implications for the health status of contemporary immigrants. Yet little is known about how such interconnectivity interacts with health.Design: In this critical ethnography study, 31 Haitian immigrants discussed the influences of transnationalism on their hypertension management. Transcripts of the semistructured individual interviews were analyzed and coded with the assistance of the Atlas.ti 6 software.Findings: Two major themes emerged: social support and financial obligation, both framed within the obligation to send monetary remittances. A duality emerged where social support facilitated hypertension self-management but consequently represented a financial burden.Discussion and implications : The study evidenced that transnationalism, although positively influencing immigrants' psychosocial well-being can negatively affect their experience with disease management. Health providers are urged to account for this transnationalism–disease management interaction when caring for this immigrant group. Future studies are needed to explore this phenomenon among other immigrant populations.